DESIGN OF A EUROPEAN SURVEY ON THE PHARMACOLOGICAL MANAGEMENT OF PAEDIATRIC HEART FAILURE. Issue 1 (14th December 2015) - Díez, Cristina Castro; Khalil, Feras; Dalinghaus, Michiel; Meulen, Marijke van der; de Wildt, Saskia; Jovanović, Ida; Bajčetić, Milica; Burch, Michel; Male, Christoph; Läer, Stephanie
Abstract : Background: Little evidence is presently available to help clinicians guide decisions when tackling the pharmacological management of paediatric heart failure (HF). As a consequence, therapeutic strategies are largely supported by adults' data extrapolation and own expertise. The variability in drug treatment routines across Europe is expected to be high. Nevertheless, there are no epidemiological data that describe the current situation. Aim: To develop a survey in the context of the LENA project to characterise the different therapeutic strategies for the management of paediatric HF that are currently practiced across Europe with special focus in the use of Angiotensin Converting Enzyme Inhibitors (ACE-I). Methods: Items to be included in the survey were selected through a thorough literature review and expert group discussions. European hospitals providing paediatric cardiology care were identified using websites of European and national paediatric cardiology associations as well as the ones of congresses and conferences related to the field. Standard recommendations for survey design were followed. The study protocol was approved by a data protection officer and an ethics committee. Web-survey tool EvaSys ® was used. The survey was pre- and pilot-tested by a group of experts. A statistical analysis plan for the later processing and analysis of the data to be obtained was elaborated. Results: A Europe-wide web-based survey was started in January 2015. 203 clinicians were invited via e-mail to participate. The questionnaire consisted of 23 questions addressing different aspects of drug therapy for HF in children. Use patterns of ACE-I (dosage by age group, effectiveness and toxicity assessment, use according to HF aetiology) and drug therapy for dilated cardiomyopathy where explored. Participants' demographic characteristics were also asked. Conclusions: The procedure followed for the survey development should assure the quality of the tool. The results of this survey will provide an overview of the clinical treatment routine of paediatric heart failure across Europe. The research leading to these results has received funding from the European Union Seventh Framework Programme (FP7/2007–2013) under grant agreement n°602295 (LENA). The following authors will also be included in the later poster: Ingrid Klingmann (PHARMAPLEX BVBA, Germany), András Szatmári (GOTTSEGEN GYORGY ORSZAGOS KARDIOLOGIAI INTEZET, Hungary), László Ablonczy (GOTTSEGEN GYORGY ORSZAGOS KARDIOLOGIAI INTEZET, Hungary), Holger Schwender (HEINRICH-HEINE-UNIVERSITÄT DÜSSELDORF, GERMANY)